If it's not what You are looking for type in the equation solver your own equation and let us solve it.
39=4x+3(2x-7)
We simplify the equation to the form, which is simple to understand
39=4x+3(2x-7)
Reorder the terms in parentheses
39=4x+(+6x-21)
Remove unnecessary parentheses
+39=+4x+6x-21
We move all terms containing x to the left and all other terms to the right.
-4x-6x=-21-39
We simplify left and right side of the equation.
-10x=-60
We divide both sides of the equation by -10 to get x.
x=6
| 1/x-7=2x | | 93-3x=24x+21 | | 204*19/51*11/16 | | 5/1+I | | x/4+6=17 | | 15/100*11500 | | 106=2x+4(-5x-5) | | 10x-3+9x+7= | | -7/6a=28 | | 9x+3=117 | | X^2+3x-6x+3x=49 | | 136+6x=-128-5x | | 3x^3-8x-11=0 | | -35-4x=6-10x | | 11-7x=63-35x | | 117=9 | | 4(x^2+1/x^2)-8(x+1/x)+3=0 | | 3x-5=10-33 | | 4x+x-8+5x+10x=12 | | x^3+11x^2-5x+1=0 | | 10+2t=3t-1 | | 2805739x-45759=583428563957489667 | | 39/49*14/99*27/26 | | 8a-5=4(3a-1) | | -6(3t-5)-4(2t+6)+4t= | | v/3-v/6=2 | | -3(2-9)+13= | | 5/6*6 | | 3(3x-1)=5(2-x)+3 | | x-56409=240021 | | x+5/6=x/2+3/4 | | (-9)(-9)(-9)= |